Effect of Engine Speeds and Dimethyl Ether on Methyl Decanoate HCCI Combustion and Emission Characteristics Based on Low-Speed Two-Stroke Diesel Engine - Wang Shiye; Yao Li (Polish Maritime Research, 2020)
The combustion and emission characteristics of homogeneous charge compression ignition (HCCI) fuelled by methyl decanoate (MD) with different engine speeds and dimethyl ether (DME) mixing ratios are investigated in this work. Engine data of a MAN B&W 6S70MC low-speed two-stroke marine diesel engine were used for the reactor. The results show that a decrease of engine speed has little effect on the in-cylinder temperature and pressure of the engine at constant excess air coefficient of 1.5. Meanwhile, NOx emissions decrease with a decrease of engine speed in pure MD HCCI combustion. The results also indicate that NOx and CO2 emissions decrease significantly with an increase in the percentage of DME in MD and DME mixing combustion at a constant total mole fraction and engine speed of 85 revolutions per minute (r/min).